KEUNIKAN KARAKTER UTAMA JAWA KUNA DALAM VISUAL BERCERITA RELIEF KARMAWIBHANGGA BOROBUDUR - Hendy Hertiasa (Wimba : Jurnal Komunikasi Visual, 2023)
The Karmawibhangga relief depicts a series of short stories embedded in a full circle at the base of Borobudur Temple in Central Java, Indonesia. Currently, the visual narrative of these reliefs is not fully understood by most cultural tourists visiting Borobudur. In any visual narrative medium, it is known that the main character becomes the focal point for the audience or readers in a story. The ability to read and interpret the main character, especially as the anchor of the story, is essential for visitors to gain a more meaningful experience and knowledge of Borobudur's cultural tourism. This study focuses on the gestures of the main and supporting characters to unfold the story. It employs an analytical approach to the visual narrative structure, examining how the events build actions and occurrences, while the existence can be represented through characters and the story's setting. The Bahasa Rupa method, specifically the Wimba and Isi Wimba techniques, is utilized to analyze the detailed and comprehensive portrayal of the visual reliefs. Additionally, the Navarasa aesthetics are used as a method to classify nine meanings of body movements, expressing both physical and mental actions of the main character. From the analysis, it is evident that most Karmawibhangga reliefs depict the daily life of ancient Javanese society, showcasing various behaviors, social stratifications, cultures, and customs. While the Navarasa aesthetics originated from ancient Indian culture and were brought to Java as a standard pattern of Hindu-Buddhist iconography, they have undergone creative transformation, becoming a unique and distinctive form of ancient Javanese aesthetics. This can be observed in the visual gestures of the main and supporting characters in the Karmawibhangga relief. One distinctive stylistic feature of the Karmawibhangga reliefs is the characteristic size of ancient Javanese human figures, which are drawn based on the tala (palm) measurement, a typical method found in Borobudur reliefs. This measurement serves as a reference in developing the main characters of the relief, allowing us to discover the uniqueness of ancient Javanese main characters in the visual storytelling of the Karmawibhangga relief at Borobudur.